ANALISIS ELASTISITAS PERMINTAAN TERHADAP KREDIT KONSUMSI DI SUMATERA UTARA - Paulina Putri A. Hutagalung; Inggrita Gusti Sari Nasution (Departemen Ekonomi Pembangunan USU, 2013)
ABSTRACT This research aims to analyze the elasticity of demand for consumer loans in North Sumatra. The variables observed in this study is consumer credit interest rate, Gross Domestic Product (GDP) per capita and the exchange rate of rupiah against the dollar. This research uses time series data for the period 1996-2010, which is a secondary data. The data is sourced from the central bank of Indonesia and North Sumatra Central Bureau of Statistics, The model used in this study is a model of multiple regression equations and analyzed using Ordinary Least Squares (OLS). Based on the estimates, the researh found that the Gross Domestic Product (GDP) per capita and the rupiah exchange rate against the dollar significantly influence credit demand in North Sumatra but consumer credit interest ratenot significantly influence. The elasticity of demand for consumer credit in North Sumatra is inelastic to changes in consumer credit interest rate and the exchange rate of the rupiah against the dollar, but it is elastic to GDP per capita. This means that the demand for consumer loans in North Sumatra are more sensitive to changes in GDP per capita than the changes in interest rates and the exchange rate againstthedollar. Keywords: Elasticity of demand, consumer credit, interest rates, GDP per capita, exchange rate.